Cephalometric evaluation of the length and deflection of the anterior cranial base in patients with different skeletal patterns - Flores Angeles, Adara (2017)
Objective: To evaluate the differences in length and deflection of the anterior cranial base in patients with different skeletal patterns, was the objective of the investigation. Materials and method: The study design was observational, descriptive and cross-sectional. The sample was conformed by 310 cephalometric radiographs of 6 to 12 year-old patients divided into three groups. Cephalometric radiographs were evaluated through the cephalometric tracing. The variables evaluated were: length of the sella-nasion line and the angle formed between the sella-nasion line and Frankfort horizontal plane. Data were statistically analyzed using the Kruskal-Wallis and U Mann-Whitney tests (p <0.05). Results: It was found significant differences in length and deflection of the anterior cranial base of skeletal class III group (60.40+4.31 mm, 7+2.11°) compared to class I group (68.36+3.76 mm, 8.13+2.64°) and Class II group (68.76+3.56 mm, 8.63+2.43°). The length and deflection of the anterior cranial base showed significant differences according to gender, but not in relation to age. Conclusions: The length and deflection of the anterior cranial base is similar in children with skeletal pattern of class I and class II but different in class III.